Conducão eletrônica e propriedades termodinâmicas da molécula de DNA - Sarmento, Ricardo Gondim (2012)
In this thesis, we study the thermo-electronic properties of the DNA molecule. For this purpose, we used three types of models with the DNA, all assuming a at geometry (2D), each built by a sequence of quasiperiodic (Fibonacci and / or Rudin-Shapiro) and a sequence of natural DNA, part of the human chromosome Ch22. The first two models have two types of components that are the nitrogenous bases (guanine G, cytosine C, adenine A and thymine T) and a cluster sugar-phosphate (SP), while the third has only the nitrogenous bases. In the first model we calculate the density of states using the formalism of Dyson and transmittance for the time independent Schr odinger equation . In the second model we used the renormalizationprocedure for the profile of the transmittance and consequently the I (current) versus V (voltage). In the third model we calculate the density of states formalism by Dean and used the results together with the Fermi-Dirac statistics for the chemical potential and the quantum specific heat. Finally, we compare the physical properties found for the quasi-periodic sequences and those that use a portion of the genomic DNA sequence (Ch22).